Exponential inequalities for exit times for two dimensional stochastic tidal dynamics equations. Issue 2 (4th March 2022) - Mohan, Manil T.
Abstract: In this work, we consider two dimensional stochastic tidal dynamics equations in bounded domains. We establish the exponential estimates on certain exit times associated with the solution trajectory of the tidal dynamics system. Using contraction principle, we study these exponential estimates of exit times in the context of a Wentzell-Freidlin type large deviations principle.